Comparison of Retrospective and Prospective Falls Reporting Among Community-Dwelling Older People: Findings From Two Cohort Studies - Romli, Muhammad Hibatullah; Mackenzie, Lynette; Tan, Pey June; Chiew, Re On; Tan, Shun Herng; Tan, Maw Pin (Frontiers in Public Health, 2021)
Background: While prospective recording is considered as the gold-standard, retrospective recall is widely utilized for falls outcomes due to its convenience. This brings about the concern on the validity of falls reporting in Southeast Asian countries as the reliability of falls recall has not previously been studied. This study aimed to evaluate the reliability of retrospective falls recall compared to prospective falls recording. Methods: A secondary analysis of data from two prospective recording methods, falls diary and falls calendar from two different research projects were obtained and analyzed. Retrospective falls recall was collected either through phone interview or follow-up clinic by asking the participants if they had fallen in the past 12 months. Results: 268 and 280 elderly participated in the diary and calendar groups respectively. Moderate (46%) and poor (11%) return rates were found on completed diary and calendar recording. Under- (32%) and over-reporting (24%) of falls were found in diary compared to only 4% of over-reporting for the calendar. Retrospective recall method achieved 57% response rate for diary group (followed-up at clinic) and 89% for calendar group (followed-up via telephone interview). Agreement between retrospective and prospective reporting was moderate for the diary (kappa=0.44; p<0.001) and strong in the calendar (kappa=0.89; p<0.001). Conclusion: Retrospective recall is reliable and acceptable in an observation study within healthy community older adults, while the combination of retrospective and prospective falls recording is the best for an intervention study with frailer older population. Telephone interview is convenient, low-cost and yielded a high response rate.